Effectiveness of a mindfulness-based training program to improve creative self-efficacy among a sample of secondary school students - Mahasneh, Ahmad M.; Gazo, Ahmad M. (Creativity Studies, 2025)
To motivating creativity among students, creative self-efficacy is one of the most important indicators, as it refers to individuals’ beliefs about their creative abilities, their motivation towards creativity, and possession of the necessary knowledge for creativity. The main objective of this study is to identify the effectiveness of a training program based on mindfulness, in improving creative self-efficacy. 30 eighth grade students, experimental and control groups included 15 students. The training program experimental group received a training program of 13 sessions, while the control group was not included. Assessment using the creative self-efficacy scale showed that the experimental group students scored higher on the creative self-efficacy table and its subscales than the students in the control group, and showed a positive effect of the mindfulness-based training program in improving creative self-efficacy among a group of secondary school students.